Poetics of Wonder - de Nie Giselle (Brepols (éditions), 2011)
The unexpected return of contemporary public Christian miracles in the late antique Latin west, after a centuries-long assumption that these had ceased after apostolic times, helped to create a religious mentality there that would continue to characterize the western European Middle Ages. While the social and political functions of the new miracles have been gaining greater scholarly attention, this study is the first in-depth treatment of their experiential dimension. It examines this dimension in the first reactions to the new phenomenon - enthusiasm, puzzlement, deep suspicion, and outright rejection - as they are reflected and, especially, imagined in the earliest contemporary narrative and poetic sources that describe them. And it traces how the new imaginative representations transformed, for many, the up to then precept-centered way of thinking about religion into one that immersed itself in the supralogical dynamics of symbolic images. The tendency of these image-clusters to precipitate transformations, not only in perception but also in physical condition, is examined for the period from 386, when a first public miracle caught everyone s attention in the ostensibly flourishing Christian Roman Empire, to c. 460, when this empire was crumbling under the onslaught of Germanic tribes.
Keywords: Philosophy; History; Social Studies; Religious Studies